The origin and evolution of Neotropical Primates - Tejedor, Marcelo Fabian (2008)
A significant event in the early evolution of Primates is the origin and radiation of anthropoids, with records in North Africa and Asia. The New World Primates, Infraorder Platyrrhini, have probably originated among these earliest anthropoids morphologically and temporally previous to the catarrhine/platyrrhine branching . The platyrrhine fossil record comes from distant regions in the Neotropics. The oldest are from the late Oligocene of Bolivia, with difficult taxonomic attribution. The two richest fossiliferous sites are located in the middle Miocene of La Venta, Colombia, and to the south in early to middle Miocene sites from the Argentine Patagonia and Chile. The absolute ages of these sedimentary deposits are ranging from 12 to 20 Ma, the oldest in Patagonia and Chile. These northern and southern regions have a remarkable taxonomic diversity and several extinct taxa certainly represent living clades. In addition, in younger sediments ranging from late Miocene through Pleistocene, three genera have been described for the Greater Antilles, two genera in eastern Brazil, and at least three forms for Río Acre. In general, the fossil record of South American primates sheds light on the old radiations of the Pitheciinae, Cebinae, and Atelinae. However, several taxa are still controversial.